(untitled) (The Peerian Journal, 2022)
The work studied the safety rules in the food industry. The characteristics of dangerous and harmful production factors, measures to combat noise, the requirement of labor protection in the bakery, pasta, and confectionery industries are given. The safety rules in the production of caramel, dragee, sweets, toffee and chocolate are widely covered.